Endoscopic treatment of pancreatic fluid collection in gastric heterotopic pancreas. A case report - Mikoviny Kajzrlíková, Ivana; Kuchař, Jan; Vítek, Petr; Hořavová, Barbora; Vaňková, Hana; Chrostek, Martin (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
BACKGROUND: Heterotopic pancreas is defined as pancreatic tissue located outside the pancreatic parenchyma that lacks an anatomic or vascular connection to the normal pancreas. Symptomatic gastric heterotopic pancreas is a rare condition that can manifest as acute or chronic pancreatitis. Asymptomatic heterotopic pancreas does not require treatment, while symptomatic lesions should be resected. The modality of final resection of heterotopic pancreas depends on its size and the depth of gastric wall involvement. METHODS AND RESULTS: A 36-year-old woman was admitted for recurrent epigastralgia. Abdominal computed tomography (CT) scan revealed that an abscess had formed in the gastric antrum. After multidisciplinary discussion we decided for conservative treatment with intravenous antibiotics and further detailed endoscopic diagnostic. Esophagogastroduodenoscopy revealed a submucosal mass with a central fistula and intermittent pus secretion in the prepyloric region of the gastric antrum, which was subsequently drained with a double pigtail stent under endoscopic ultrasound (EUS) and fluoroscopy. The possibility of pancreatic fluid collection in the case of heterotopic pancreas was suggested during the EUS examination, and histology subsequently confirmed heterotopic pancreatic tissue. The patient was in good condition and without any abdominal pain. According to a control CT scan after 10 weeks, the fluid collection was completely resolved. Due to the possible recurrence of pancreatitis, resection of heterotopic pancreas was proposed to the patient. Since the lesion involved the muscularis propria of the gastric wall, surgical resection of the mass was indicated. CONCLUSION: Fluid collections after acute pancreatitis in heterotopic pancreas in the gastric antrum can be successfully managed by endoscopy.
Keywords: ženské pohlaví; Acute Disease; Female; pankreatitida; lidé; Endoscopy; endoskopie; Adult; endosonografie; akutní nemoc; pankreas; dospělí; Humans; Pancreas; Endosonography; Pancreatitis